Cyberfeminisms and the creative reorganization of activism in the digital era: an analysis of Brazilian profiles on Instagram in Portugal (TEL Tempo, Espaço e Linguagem, 2024)
In recent years, especially during the Covid-19 pandemic, there has been a boom in profiles and pages related to feminisms in cyberspace, especially on Instagram. The emergence of cyberfeminisms contributes to the popularization of feminist agendas and the internationalization of solidarity between women. This study combines the work of authors such as Haraway (1991), Hollanda (2018), Gago (2020) and Mohanty (2013) with recent work on platformization and activism in the digital era (Van Dijck, Poell & De Waal, 2018; Castells, 2013), in an attempt to understand how cyberfeminisms contribute to the agenda of the current phase of feminisms. To do this, it will analyze the Instagram profiles: @PlataformaGeni and @ColetivoAndorinha between the years 2021 and 2024, through a qualitative netnographic approach (Kozinets, 2015). The selected profiles are part of the context of cyberfeminism in Portugal and Brazil, as they are organized by Brazilian women who live in Lisbon.Keywords: Cyberfeminism. Social Media. Instagram. Digital Activism. Feminisms.